Gordon Growth Model with Vector Autoregressive Process - Gankhuu, Battulga (Mongolian Mathematical Journal, 2024)
In this study, we introduce a Gordon’s dividend discount model, based on Vector Auto Regressive Process (VAR). We provide two Propositions, which are related to the generic Gordon growth model and the Gordon growth model, which is based on the VAR process.